Suprapatellar versus infrapatellar nailing for tibial shaft fractures: A comparison of surgical and clinical outcomes between two approaches - Al-Azzawi, M. (J Clin Orthop Trauma, 2021)
BACKGROUND: Tibial shaft fractures are a relatively common injury and contemporary treatment includes on-axis fixation with a locked intramedullary nail in the majority of cases. The conventional technique is via an infrapatellar approach but currently there is a trend towards the use of a suprapatellar approach. We compared key variables including operative time, radiation exposure and early patient reported outcomes when adopting a suprapatellar approach to tibial nailing in our unit versus our previous experience of infrapatellar tibial nailing. METHOD: Twenty-eight consecutive patients with tibial fracture underwent tibial nailing via the suprapatellar (SPN) approach. Six patients in the study group were excluded due polytrauma and need for dual orthopaedic and plastic surgery management. We compared outcomes with our most recent 20 consecutive patients who had undergone tibial nailing via an infrapatellar (IPN) approach. Primary surgical outcomes were: operative time, radiation exposure and accuracy of entry point of the nail on both anteroposterior and lateral radiographs. Clinical outcomes included time to weightbearing, time to radiographic union and patient-reported outcome score (Lysholm score). RESULTS: Forty-eight consecutive patients underwent intramedullary nail fixation for tibial shaft fractures and 42 were eligible for inclusion in our study (22 SPN vs 20 IPN). There were no significant differences in patient demographics or injury patterns between the two groups. Operative time and radiation exposure were significantly lower in the SPN group when compared to the IPN group (115 min vs 139 min ± 12.5) (36 cGY/cm(2) vs 76.33 cGY/cm(2) +/- 20.1). Furthermore, patients in the SPN group reported superior outcome scores at a mean follow up of 3 months (8–24 weeks) There were no observed differences in complication rate between groups and time of final clinical follow up at a minimum of 6 months. CONCLUSION: Our study shows that adoption of the SPN approach requires minimal learning curve, and has the potential benefits of reduced operative time, radiation exposure and superior patient reported outcomes when compared to the conventional infrapatellar approach.